Psychometric properties of the Spanish version of the Pediatric Quality of Life Inventory Family Impact Module (PedsQL FIM) - Javiera Ortega; Natalia Vázquez; Imanol Amayra Caro; Florencia Assalone (Elsevier, 2023)
Introduction: This study analysed the psychometric properties of the Spanish version of the Pediatric Quality of Life Questionnaire Family Impact Module (PedsQL FIM) in the Argentinian population. Patients and Methods: The sample included 232 caregivers, of who 108 were parents of children with chronic diseases (mean, 9.54; standard deviation [SD], 4.43) and 124 parents of children in the general population (mean, 12.37; SD, 4.6). Results: We assessed the validity of the instrument with the known-groups method, finding significant differences between the case and control groups in the overall and subscale scores (P < .01). We also assessed test validity by means of exploratory factor analysis, which yielded an 8-factor model that explained 74.03% of the variance. We assessed reliability with the Cronbach alpha and found a high internal consistency (α = 0.95). Conclusion: The PedsQL module proved to be a valid and reliable tool to assess the impact of a chronic paediatric condition on caregiver quality of life and family functioning. Resumen: Introducción: Este trabajo analiza las propiedades psicométricas de la versión en castellano del Cuestionario de Calidad de Vida Pediátrica Módulo de Impacto Familiar (PedsQL FIM) en población argentina. Pacientes y Métodos: Se obtuvo una muestra de 232 cuidadores, 108 de niños con enfermedades crónicas (M = 9,54, DE = 4,43) y 124 de niños de población general (M = 12,37, DE = 4,6). Resultados: La validez del instrumento se estudió a través del método de grupos contrastados, encontrando diferencias significativas en la escala total y subdimensiones de la escala (p < 0,01). A su vez, se realizó un análisis factorial exploratorio en el que se encontró un modelo de 8 factores explicando el 74,02% de la varianza total. La confiabilidad fue estudiada a través del Coeficiente Alfa de Cronbach y se encontró un valor alto de consistencia interna α = 0,95. Conclusiones: El instrumento PedsQL demostró ser una herramienta válida y confiable para estudiar el impacto que tiene una condición pediátrica crónica a nivel de la calidad de vida del cuidador y del funcionamiento familiar.